Control of the tutorial measures in the accompaniment of the service of support and advice for the attention of the educational needs - Fuster Guillen, Doris Elida (2017)
The research called "Control of tutorial measures in the accompaniment of SAANEE in the educational institutions of Lima and Callao" arises with the intention of knowing how the professionals that make up this service, contribute to the teaching work that they have under their responsibility the training of students with some disability, also develop an adequate tutorial action through the accompaniment in the implementation of tutorial measures. The purpose of this study was to determine the predominant dimension of control of tutorial measures in the accompaniment of SAANEE, developed with the positivist paradigm, quantitative approach, noun type, descriptive and explanatory, non - experimental design. The sample was formed by 40 tutors from the educational institutions of Lima and Callao. The results were processed through linear regression, demonstrating that the predominant dimension is the control of the work of the Service of Attention to Students with Special Educational Needs (SAANEE).